Management of Anesthesia under Extracorporeal Cardiopulmonary Support in an Infant with Severe Subglottic Stenosis - Rie Soeda; Fumika Taniguchi; Maiko Sawada; Saeko Hamaoka; Masayuki Shibasaki; Yasufumi Nakajima; Satoru Hashimoto; Teiji Sawa; Yoshinobu Nakayama (Case Reports in Anesthesiology)
A 4-month-old female infant who weighed 3.57 kg with severe subglottic stenosis underwent tracheostomy under extracorporeal cardiopulmonary support. First, we set up extracorporeal cardiopulmonary support to the infant and then successfully intubated an endotracheal tube with a 2.5 mm inner diameter before tracheostomy by otolaryngologists. Extracorporeal cardiopulmonary support is an alternative for maintenance of oxygenation in difficult airway management in infants.